Catechol-O-methyltransferase Val158Met genotype and the clinical responses to duloxetine treatment or plasma levels of 3-methoxy-4-hydroxyphenylglycol and homovanillic acid in Japanese patients with major depressive disorder - Atake K (Dove Medical Press, 2015)
Kiyokazu Atake, Reiji Yoshimura, Hikaru Hori, Asuka Katsuki, Jun Nakamura Department of Psychiatry, University of Occupational and Environmental Health, Kitakyushu, Fukuoka, Japan Purpose: This study investigated the relationships among the plasma levels of catecholamine metabolites, the clinical response to duloxetine treatment, and Val158Met polymorphism of the catechol-O-methyltransferase (COMT) gene. Subjects and methods: Sixty-four patients and 30 healthy control subjects were recruited. Major depressive episodes were diagnosed using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision criteria. The severity of depression was evaluated using the 17-item Hamilton Rating Scale for Depression (HAMD17). Patients whose HAMD17 scores were 15 or greater were enrolled in the study. Blood sampling and clinical evaluation were performed at week 0 and week 8. The levels of plasma catecholamine metabolites were measured using high-performance liquid chromatography with electrochemical detection. Genotyping was performed using direct sequencing. Results: Thirty of 45 patients (67%) responded to duloxetine treatment during the 8 weeks of treatment. The baseline plasma levels of 3-methoxy-4-hydroxyphenylglycol (MHPG), but not homovanillic acid (HVA), were lower in patients with major depressive disorder (MDD) who had the Val/Val genotype than in patients who were Met-carriers. Patients with MDD and the Val/Val genotype, but not Met carriers, had increased plasma levels of MHPG after 8 weeks of duloxetine treatment. The baseline plasma MHPG levels in healthy control subjects with the Val/Val genotype were significantly higher than those in patients with MDD. Among the subjects in the MDD group with the Val/Val genotype, the plasma MHPG levels increased to the same degree as in the healthy control subjects with the Val/Val genotype after 8 weeks of duloxetine treatment. Conclusion: The relationship among the COMT Val158Met polymorphism, plasma levels of catecholamine metabolites, and responses to duloxetine is complex. Nevertheless, our results suggest that patients with MDD and the Val/Val genotype are more sensitive to the influence of noradrenergic neurons by duloxetine treatment. Keywords: major depressive disorder, duloxetine, catechol-O-methyltransferase, 3-methoxy-4-hydroxyphenylglycol, homovanillic acid